2012
DOI: 10.3329/jhpn.v30i3.12293
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Breastfeeding and Obesity in Childhood

Abstract: A cross-sectional study was conducted to investigate the weight status and the relationship of infant-feeding variables, birthweight and birth order with BMI in a group of Iranian children. Five hundred and eleven students of both sexes at the first grade in elementary schools (aged 7 years) were recruited randomly from all 19 educational districts of Tehran. Weights and heights of children and their mothers were measured. Data on breastfeeding (BF), formula-feeding, the timing of introduction of complementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 34 publications
2
20
0
9
Order By: Relevance
“…Полученные показатели интерпретировались с помощью классификации, основанной на Z-скор (единицы стандартного отклонения (СО) от средне-го стандарта). Стандартное распределение Z-скор ПРОБЛЕМЫ ЭНДОКРИНОЛОГИИ, 4,2014 для каждого показателя имеет среднее 0,0 и стан-дартное отклонение 1,0. Значение Z-скор, равное +1, соответствует 84,5-му процентилю при стан-дартном распределении, тогда как Z-скор, равный 2, соответствует 97,7-му процентилю стандартного распределения.…”
Section: материал и методыunclassified
See 2 more Smart Citations
“…Полученные показатели интерпретировались с помощью классификации, основанной на Z-скор (единицы стандартного отклонения (СО) от средне-го стандарта). Стандартное распределение Z-скор ПРОБЛЕМЫ ЭНДОКРИНОЛОГИИ, 4,2014 для каждого показателя имеет среднее 0,0 и стан-дартное отклонение 1,0. Значение Z-скор, равное +1, соответствует 84,5-му процентилю при стан-дартном распределении, тогда как Z-скор, равный 2, соответствует 97,7-му процентилю стандартного распределения.…”
Section: материал и методыunclassified
“…Нужно отме-тить, что сельское население нашей страны неохот-но готовит пищу отдельно для ребенка. Так, каши давали всего лишь 35,8% в 1-й и 35,1% во 2-й группе детей (в основном рисовую и манную домашнего ПРОБЛЕМЫ ЭНДОКРИНОЛОГИИ, 4,2014 приготовления). К сожалению, до сих пор традици-онно в сельской местности детей кормят мучной смесью (4,7 и 5,4% в 1-й и 2-й группе соответствен-но).…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation
“…Not breast feeding a child or shortened breast feeding duration : Several studies have shown that babies who were not breastfed at all but rather fed on infant formula, or babies who had very short duration of breastfeeding, had a higher rates of obesity and overweight compared to babies breast fed for long duration [69]. Prolonged and exclusive breastfeeding on the other hand have been suggested to be protective factors in obesity in children, [70][71][72][73][74][75][76][77]. There is also high risk of obesity in both mothers and babies if mothers did not breast feed [78].…”
Section: H Insufficient Dietary Calcium: Consumption Of Insufficientmentioning
confidence: 99%
“…Food portion sizes; increased food consumption [47][48][49] High intake of total fat, saturated fat and trans fat [50,51] Fast food/Fried foods, [52][53][54][55] Junk food [56][57] -Soft drinks (sodas and sweetened beverages); -high caloric drinks,( sweetened & caffeinated beverages, juices, sugary drinks, juice blends); -Energy drinks [57][58][59][60][61] Alcoholic drinks [62] Overeating, binge eating, mindless eating and excessive snacking [56,62,63] Consumption of High fructose corn syrup and artificial sweeteners [55,59,[62][63][64] Insufficient dietary calcium intake or low dairy intake [67] Low intake of fiber , and Low intake of fruits and vegetables in foods [68,69] Not breastfeeding or short breastfeeding duration ; formula feeding instead of breastfeeding [70][71][72][73][74][75][76][77][78] Intestinal microbes [79][80][81][82][83] Antibiotics in human foods [84][85]…”
Section: Possible Dietary and Related Factors That Cause Obesity/overwementioning
confidence: 99%